Functional expression of the lactate permease Jen1p of Saccharomyces cerevisiae in Pichia pastoris - Silva, Isabel Soares (2003)
In Saccharomyces cerevisiae the activity for the lactate proton-symporter in dependent on JEN1 gene expression. Pichia pastoris was transformed with an integrative plasmid containing the JEN1 gene. After 24 h of methanol induction, Northern and Western-blotting analyses indicated the expression of JEN1 in the transformants. Lactate permease activity was obtained in P. pastoris cells with a Vmax of 2.1 nmol s-1 mg-1 dry weight. Reconstitution of the lactate permease activity was achieved by fusing plasma membranes of P. pastoris methanol-induced cells with Escherichia coli liposomes containing cytochrome c oxidase, as proton-motive force. These assays in reconstituted heterologous P. pastoris membrane vesicles demonstrate that S. cerevisiae Jen1p is a functional lactate transporter. Moreover a S. cerevisiae strain deleted in the JEN1 gene was transformed with a centromeric plasmid containing JEN1 under the control of the glyceraldehyde 3-phosphate dehydrogenase constitutive promotor. Constitutive JEN1 expression and lactic acid uptake were observed in cells grown either on glucose and/or acetic acid. The highest Vmax (0.84 nmol s-1 mg-1 dry weight) was obtained in acetic acid-grown cells. Thus overexpression of the S. cerevisiae JEN1 gene in both S. cerevisiae and P. pastoris cells resulted in increased activity of lactate transport when compared to the data previously reported in lactic acid-grown cells of native S. cerevisiae strains. Jen1p is the only S. cerevisiae secondary porter characterized so far by heterologous expression in P. pastoris at both the cell and membrane vesicle levels.